Predictors of Marital Satisfaction in Individualistic and Collectivist Cultures: A Mini Review - Kaizm, Syed Musa; Rafique, Rafia (Asia Pacific Journal of Social Science Research, 2022)
This article highlights key empirical and conceptual progress in understanding of predictors of marital satisfaction. The article brings together studies in this area summarizing the key findings, and then focuses on comparison of marital satisfaction predictors across individualistic and collectivist cultures. The researches on marital relationships currently addresses the concepts like satisfaction, marital success, consensus, companionship, adjustment, quality or some concepts relevant to satisfaction of marital life. All the common and different predictors of marital satisfaction are identified and compared with the existing body of literature in individualistic and collectivistic cultures. Although there are some conflicting findings that hinder drawing of conclusive evidence, we found predictors of marital satisfaction among that are shared between individualistic and collectivist cultures. Hence some universal predictors of marital happiness are highlighted through cultural comparison. After this review the future researchers and counselors will be well aware of cross cultural predictors of marital satisfaction which will help them in future conductance of researches and couple’s counseling.Keywords:Marital satisfaction, individualistic, collectivistic culture, cross culture comparison